Isolation and Identification of Fungal Propagation in Iraqi Meat and Detection of Aflatoxin B1 Using ELISA Technique - Rawaa Emad Jaloud (Journal of Global Pharma Technology, 2018)
The study was conducted at the College of Education for Pure Sciences (Ibn Al-Haitham /University of Baghdad. The aim of this study was to isolate and diagnose fungi from meat samples and detection of aflatoxin B1. The samples included different types of sheep meat that collected from the local slaughter areas and government approved in Baghdad (Al-Karkh and Al-Rusafa); this study included the collection of 50 samples from fresh sheep meat (25 liver and 25 triceps muscles), 13 of minced meat and 12 of basterma samples. Two methods of isolation were used which are direct and indirect to detect Fungi in the samples; the results have been found the presence of various genus of fungi including Aspergillus spp., Penicillin spp.,Rhizopusspp.,Mucorspp.,Cladosporiumspp.,Fusariumspp.,Moniliaspp., Botrytis spp., Trichothecium spp., Ulocladium spp. And Yeast spp. According to the type of isolation method, Aspergillus spp. is the most common genus that isolated from the samples using direct method, while yeast was the most predominant in the samples using indirect method in all samples except in the muscles where Aspergillus spp. Were the predominant fungi in both isolation methods? Results of the detection of aflatoxin B1 showed that 71 of the samples were contaminated with toxin; the samples included minced meat, basterma, liver and muscles with different concentrations of aflatoxin ranging from 42-467 ppb, 25-442 ppb, 44-492 ppb and 242-459 ppb for respectively.